Innovative PIN-type perovskite solar cells with 17% efficiency: processing and characterization. Issue 24 (21st October 2021) - Lemercier, T.; Perrin, L.; Berson, S.; Flandin, L.; Planes, E.
Abstract : We optimized the deposition conditions of the PK layer. Changing first the antisolvent ejection time and then the drying time the PCE jumped from 10% to 17%. We propose a protocol to perform the optimization by removing pinholes at different scales. Abstract : To develop high-performance tandem cells, it seems necessary to optimize semi-transparent PSC single junctions with a PIN-type architecture. In this article, the development of this PIN-type architecture by the optimization of the Hole Transport Layer (HTL) is proposed. Firstly a study of three HTLs with different surface properties such as PEDOT:PSS, PTAA and TFB was carried out, to understand their influence on the deposition conditions and on the final properties of the deposited perovskite layer. Indeed, the use of layers such as PTAA and TFB represents a real alternative, already mentioned as very promising in NIP and PIN type architectures. But unlike PEDOT:PSS, these hydrophobic layers disrupt the deposition of the perovskite layer. Once the material was chosen the HTL, here TFB, which has real originality, the optimization of the process was carried out. The latter based on the evaluation of the antisolvent ejection time and the drying time allowed a drastic increase in the PCE from 10% to 17%. Another important result of this study is the methodology used for this optimization. Indeed, the main marker used is the observation of defects in the perovskite layer at the macroscopic and microscopic scales. This optimization of the perovskite layer morphology leads to a significant increase in performance. This approach will be very useful to the community for a possible optimization of other devices.